The use of artificial intelligence for teaching and learning in public health: concrete perspectives - Araújo Carvalho, Jéssica (2025)
Introduction: The use of Artificial Intelligence (AI) arises with the potential to collaborate with Education and Science, transiting between a dialectical matrix of aggrandizement of the action of learning and teaching through the optimization of its processes, but it also presents challenges for this teaching-learning relationship in the field of Collective Health, due to the way this technology can be used and the lack of regulation that accompanies its rapid development. Study proposal: To analyze the use of Artificial Intelligence in the teaching-learning process in the field of Collective Health, by students and educators, from a dialectical perspective. Discussion: This is a critical-reflective theoretical essay, presented in two problematized axes, namely: the concrete context of teaching-learning in the face of the use of AI in Collective Health: Challenges about its use in teaching-learning in Collective Health; and the relationship between the new and the fetish about its use in the future of Collective Health. Final Considerations: It is concluded that the use of Artificial Intelligence cannot be denied as a tactic to achieve a dialectic of teaching-learning-teaching-learning, however, its use needs to overcome the barriers of irrational instrumentality due to the absence of reflection and criticism, essential attitudes for the field of Collective Health, avoiding the destructive traps of alienated activity/work.